2019
DOI: 10.1097/cce.0000000000000034
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an ICU Recovery Clinic at a Tertiary Care Academic Center

Abstract: Objectives: Post-ICU clinics may facilitate the care of survivors of critical illness, but there is a paucity of data describing post-ICU clinic implementation. We sought to describe implementation of our ICU recovery clinic, including an assessment of barriers and facilitators to clinic attendance. Design: Adults admitted to the medical ICU of a large tertiary care academic hospital with shock and/or respiratory failure requiring mechanical ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Our ICU recovery clinic consists of a transdisciplinary team that includes a physician, an advanced practice registered nurse (APRN), a pharmacist, a physical therapist, and a social worker focused on improving quality of life after critical illness, organizing subspecialty follow-up care, and promoting rehabilitation. The primary objectives of ICU follow-up or recovery clinics are to address and treat post–intensive care syndrome (PICS) and help patients reintegrate into their societal roles following an admission to the ICU [ 4 7 ]. Post-ICU follow-up clinics also address traumatic emotional experiences of family members and engage all parties to optimize outcomes [ 8 – 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our ICU recovery clinic consists of a transdisciplinary team that includes a physician, an advanced practice registered nurse (APRN), a pharmacist, a physical therapist, and a social worker focused on improving quality of life after critical illness, organizing subspecialty follow-up care, and promoting rehabilitation. The primary objectives of ICU follow-up or recovery clinics are to address and treat post–intensive care syndrome (PICS) and help patients reintegrate into their societal roles following an admission to the ICU [ 4 7 ]. Post-ICU follow-up clinics also address traumatic emotional experiences of family members and engage all parties to optimize outcomes [ 8 – 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some published studies of this type of clinic have shown attendance rates below 50%. [45][46][47] This study has potential limitations. First, participants' prehospitalization health, physical function, and quality of life status were obtained from retrospective interviews, which may have introduced recall bias.…”
Section: Before Hospitalizationmentioning
confidence: 96%
“…Several countries have invested significant efforts into ICU follow-up clinics to help support recovery following critical illness in adults (132)(133)(134)(135). ICU follow-up clinics usually require the patient to attend the hospital to see a combination of interdisciplinary professionals, who assess progress in all PICS domains, provide medication therapy review, reconciliation and counselling, and coordinate care and communication with primary care providers and other specialists as needed.…”
Section: What Is the Best Format For Follow-up?mentioning
confidence: 99%